2001
DOI: 10.1071/ea00081
|View full text |Cite
|
Sign up to set email alerts
|

The current and potential contribution of asymbiotic nitrogen fixation to nitrogen requirements on farms: a review

Abstract: Significant levels of biological nitrogen fixation from sources other than nodulated legumes have become a tantalizing prospect for decades. Since the benefit to agriculture of nitrogen fixation from nodulated legumes was established, there have been widespread efforts to promote the use of various asymbiotic diazotrophic bacteria to fix extra nitrogen in soil. Despite much optimism by scientists and farmers, this prospect remains to be realised. Recently, the prospect has been pursued with renewed enthusiasm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 88 publications
1
32
0
1
Order By: Relevance
“…The %N (N derived from the atmosphere) values were 19.5-38.7, and 38.1-58.2 in basmati and super basmati, respectively. Herbaspirillum seropedicae also acts as an endophytic diazotroph of wheat plants (Kennedy and Islam 2001), colonizing wheat roots internally between the cells. Herbaspirillum seropedicae is also found in roots and stems of sugarcane plant while Herbaspirillum rubrisubalbicans is an obligate endophyte of roots, stems and leaves (Reis et al 2000).…”
Section: Symbiotic N 2 -Fixing Bacteriamentioning
confidence: 99%
“…The %N (N derived from the atmosphere) values were 19.5-38.7, and 38.1-58.2 in basmati and super basmati, respectively. Herbaspirillum seropedicae also acts as an endophytic diazotroph of wheat plants (Kennedy and Islam 2001), colonizing wheat roots internally between the cells. Herbaspirillum seropedicae is also found in roots and stems of sugarcane plant while Herbaspirillum rubrisubalbicans is an obligate endophyte of roots, stems and leaves (Reis et al 2000).…”
Section: Symbiotic N 2 -Fixing Bacteriamentioning
confidence: 99%
“…These values are very speculative but, with current knowledge, it is impossible to offer alternatives. A number of reviews of plant-associated N 2 fixation have clearly highlighted the many methodological problems and inconsistencies in the published studies (Boddey 1987;Chalk 1991;Giller 2001;Kennedy and Islam 2001;Giller and Merckx 2003). One of the key problems is distinguishing between inputs of N by free-living and associative agents and other external sources of N contributing to agricultural soils, e.g.…”
Section: Forage/fodder Legumes-rhizobiamentioning
confidence: 99%
“…For example, Giller (2001) concluded that N 2 fixation by free-living bacteria would rarely exceed 5 kg N/ha/year. However, none of these publications offer a rate figure that could be applied globally, although Kennedy and Islam (2001) were optimistic that perceived problems in manipulating the associative systems to the point that they could be utilised more effectively would be overcome with additional research.…”
Section: Forage/fodder Legumes-rhizobiamentioning
confidence: 99%
“…On a global scale asymbiotic nitrogen fixation (ANF) contributes to about 30% to the total biologically fixed N, and can play a significant role in many terrestrial ecosystems (Cleveland et al, 1999). However, in an agricultural context, symbiotic BNF by legumes is considered to be by far the most dominant source of biologically fixed N (Kennedy and Islam, 2001). Other symbiotic systems with agricultural applications include the Azolla-Nostoc (Vaishampayan et al, 2001), and the Frankia-Alder symbioses (Paul and Clark, 1996).…”
Section: Contribution Of Biological Nitrogen Fixation In Nitrogen Reqmentioning
confidence: 99%
“…Other symbiotic systems with agricultural applications include the Azolla-Nostoc (Vaishampayan et al, 2001), and the Frankia-Alder symbioses (Paul and Clark, 1996). All of these symbioses are genetically defined systems that include specific interactions between diazotroph and host-plant (Kennedy and Islam, 2001). …”
Section: Contribution Of Biological Nitrogen Fixation In Nitrogen Reqmentioning
confidence: 99%